2011
DOI: 10.1097/ta.0b013e318202f1d0
|View full text |Cite
|
Sign up to set email alerts
|

Subtalar Arthroscopy and Flurosocopy in Percutaneous Fixation of Intra-Articular Calcaneal Fractures: The Best of Both Worlds

Abstract: Subtalar arthroscopy augments intraoperative fluoroscopy in anatomic reduction of the posterior calcaneal facet of the subtalar joint and is most useful for Sanders type II, AO-OTA 83-C2 fractures. The percutaneous approach further avoids soft tissue complications associated with open reduction. However, this procedure has a steep learning curve, and conversion to open reduction must be considered when percutaneous reduction fails.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 31 publications
1
56
1
1
Order By: Relevance
“…Although the predictive value of Böhler's angle on outcome remains a subject of debate, the initial angle at the time of trauma still guides treatment [5,6]. There is a considerable amount of literature on the change of Böhler's angle following surgically treated displaced intra-articular calcaneal fractures throughout the followup (Table 1) [7][8][9][10][11][12][13][14][15][16][17]. Data on Böhler's angle in conservatively-treated fractures, however, are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Although the predictive value of Böhler's angle on outcome remains a subject of debate, the initial angle at the time of trauma still guides treatment [5,6]. There is a considerable amount of literature on the change of Böhler's angle following surgically treated displaced intra-articular calcaneal fractures throughout the followup (Table 1) [7][8][9][10][11][12][13][14][15][16][17]. Data on Böhler's angle in conservatively-treated fractures, however, are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Infection and wound complication rates for MIPO range from 0 to 11% [13,16,27,31,33]. MIPO results in a better subtalar range of motion [26,30].…”
Section: Introductionmentioning
confidence: 98%
“…In some specialized trauma or foot and ankle centers, the current trend is towards surgical management [5,[13][14][15][16]. However, recent publications have shown that conservative management outcomes mirror surgical management [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Images and surgical technique described in this section are adapted from our original article by Woon et al 9 Patients are positioned in the lateral decubitus position on the uninjured side. The suggested positioning of the image intensifier, arthroscopy equipment and personnel is shown in Figure 4 to facilitate the use of fluoroscopy and arthroscopy in our technique.…”
Section: Surgical Techniquementioning
confidence: 99%
“…9 The objective of this retrospective study is to evaluate long-term outcomes of the use of dual-modality imaging using similar evaluation parameters.…”
Section: Introductionmentioning
confidence: 99%